Análise funcional de um consórcio microbiano de solo e prospecção de genes envolvidos na desconstrução da biomassa - Lima, Milena Tavares [UNESP] (2014)
The deconstruction of lignocellulose by the action of microorganisms is an essential process for the carbon cycle and the conversion of biomass into fuels and chemicals. A wide variety of carbohydrates found in plant cell walls requires a multitude of enzymes for their degradation. The aim of this study was to isolate a microbial consortium of soil sample containing bagasse cane sugar decomposition, which is efficient in the deconstruction of biomass and the total DNA sequence for the isolation of genes involved in the deconstruction of lignocellulose. The biomass degrading microbial consortium was obtained from soil sample cultivated with sugarcane decomposed and shown to be efficient in the degradation of a potential lignocellulosic substrate, sugarcane bagasse. To prove the efficiency of the release of sugar from the biomass potential to be used in fermentation processes chromatographic analysis of sugars was performed when the number of microorganisms were cultivated only in a medium containing cane bagasse as a source of carbon. This test showed the release of glucose in the culture medium. Similarly, microbiological tests have shown that the production of hydrolytic enzymes such as cellulases and amylases have been made. The sequencing of total DNA extracted from the samples cultured in medium with cellulose consortium made possible the identification of microorganisms present in the consortium. Through these sequences to search for genes involved in the degradation of biomass and this assessment was also carried the genes of the enzymes alpha amylase, glucoamylase, alpha- glucosidase, beta glucosidase and endoglucanase enzymes of paramount importance in the process of deconstruction of lignocellulose found. All genes of the enzymes were similar to sequences of the bacterium Burkholderia sp SJ98, which has been described in the literature as an efficient organism in biodegradation of different compounds. Thus in the present ...